ANALYSIS OF ADDED VALUE OF CASSAVA INTO CASSAVA CHIPS IN SUNGAI RAYA DISTRICT, KUBU RAYA DISTRICT - Fajar, Muhamad Iqbal; Kurniati, Dewi; Pamela (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2025)
This study aims to evaluate the added value of processing cassava into cassava chips and identify market prospects. The research location was purposively selected at UMKM Cita Rasa Mandiri, which is located in Kuala Dua Village, Sungai Raya District, Kubu Raya https://www.surreyhillschallenge.com/ Regency. This research was conducted from July 2024 to August 2024. The data collected consisted of primary and secondary sources, using observation and interview techniques. Data analysis was conducted using the hayami method for added value, along with an evaluation of costs, revenues, profits, and market potential as outlined by Kotler in 1997. The results of this study show that the processing of cassava into cassava chips generates added value. The added value of processing cassava chips in UMKM Cita Rasa Mandiri reached IDR 13,210 per kilogram of raw materials, with total costs of IDR 1,056,483, resulting in revenues of IDR 2,040,000 and profits of IDR 983,517, while the market potential is estimated at IDR 926,655,000.